Developing a Strategic Sustainability Assessment Methodology for Free Zones Using the Analytical Hierarchy Process Approach - Omar Sharaf-addeen Alansary (17746719) (2023)
The application of sustainability within free zones can be considered a means to enhancing their competitiveness. Free zones with a high level of sustainability are more likely to attract investment and other kinds of support, while meeting global obligations with regard to sustainable development. Accordingly, adopting sustainability assessment tools is crucial for measuring the sustainability effectiveness of free zones. In this context, this study addresses the sustainability assessment of free zones using the analytical hierarchy process (AHP) decision tool. The first contribution of this article is proposing a novel model for the strategic sustainability assessment in free zones, which considers all dimensions of sustainability. The second contribution is deriving the weights and priorities of the related model using the AHP method. The results demonstrate that the economic dimension is considered the most regarded sustainability pillar, with a percentage of 41.81%, followed by the environmental pillar at 24.97%; then, the social pillar at 22.26%, and finally, the organizational pillar at 10.96%. Although this study addressed sustainability assessment indicators, it did not delve into the individual components deeply, which may open opportunities to direct future research toward developing other sustainability assessment models in the context of free zones. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su15139921